Geomechanics II 2006
DOI: 10.1061/40870(216)4
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Stress-Strain Behavior at Small Strains of Clay by Triaxial and Bender Element Tests

Abstract: In this study, to examine the effect of the fabric anisotropy on elastic moduli (shear and Young's moduli), the bender element, cyclic and monotonic triaxial tests were performed on reconstituted clay specimens with different fabric characteristics. The specimens with the angle between the axial direction of the triaxial specimen and the bedding direction of 0 and 90 degrees were cut from the pre-consolidated clay block. These specimens were isotropically consolidated under several kinds of confining pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…This trend tend to be reversed when the shear strain is greater than 10 -1 %. These results are in agreement with observation conducted by Yamashita et al (2003 and2005). The authors made specimen as pluviation direction of 0 o (V-specimen) and 90 o (H-specimen).…”
Section: Results On the Lss Testsupporting
confidence: 93%
See 3 more Smart Citations
“…This trend tend to be reversed when the shear strain is greater than 10 -1 %. These results are in agreement with observation conducted by Yamashita et al (2003 and2005). The authors made specimen as pluviation direction of 0 o (V-specimen) and 90 o (H-specimen).…”
Section: Results On the Lss Testsupporting
confidence: 93%
“…The ratios of (G0(a=90°)/G0(a=0°)) are 1.14 and 1.12 for unsaturated sand and saturated sand, respectively. Bellotti et al (1996), Pennington et al (1997), Yamashita et al (2005), Hight et al (2007), and Teng et al (2013) demonstrated that the shear moduli in the horizontal plane were higher than those in vertical plane. Ng and Yung (2008) proved that the increase of matric suction from 0 kPa to 50 kPa induced the increase of the shear modulus ratio (G0(hh)/G0(hv)) from 1.03 to 1.05.…”
Section: The Degree Of Anisotropymentioning
confidence: 92%
See 2 more Smart Citations